Predictive Roles of Thinking Styles in Coping Strategies Among Mainland Postgraduate Students in Hong Kong - Chen, Siyao (Frontiers in Psychology, 2022)
This study aimed at exploring the influential roles of demographic factors on thinking styles and the statistically predictive power for thinking styles in stress coping beyond demographic factors among mainland postgraduate students from a university in Hong Kong. The Thinking Styles Inventory-Revised II and COPE-Revised were administered to 148 participants (36 males and 112 females). Results indicated that thinking styles varied as a function of age, gender, gender role orientation, and marital status. Type I styles were primary predictors for adaptive stress coping strategies, and at the same time, Type II styles positively contributed to maladaptive stress coping strategies, which were largely in the expected directions. The contributions, implications, and limitations of the research are discussed.